Encanutado de bocachico como símbolo de identidad y tradición montuvia en la Provincia de Los Ríos - Luna Anchundia, Sindy Mariuxy (2025)
Encanutado de bocachico is an emblematic dish that symbolizes the identity and tradition of the Montuvian people in the province of Los Ríos. This dish, which is made using bocachico (a freshwater fish) cooked inside a guadua cane joint, has been an integral part of local culture for decades, although its practice has decreased in recent years. The preparation of encanutado involves a traditional process that includes the preparation of a refried dish with ingredients such as tomato, onion and peanuts, which is mixed with the fish before cooking it in the canutos. This method not only highlights the culinary creativity of the Montuvian people, but also reflects their connection to the natural environment and their cultural heritage. The encanutado has gained recognition both nationally and internationally, participating in gastronomic competitions that seek to establish it as a symbol of regional identity. Through these activities, we seek not only to preserve the recipe, but also to foster a sense of belonging and pride among the Montubios for their rich gastronomic heritage.